Pretreatment with the ALDH2 agonist Alda-1 reduces intestinal injury induced by ischaemia and reperfusion in mice - Zhu, Qiankun (Clin Sci (Lond), 2017)
Many studies demonstrate that activation of aldehyde dehydrogenase 2 (ALDH2) protects against oxidative stress via detoxification of cytotoxic aldehydes, and could attenuate cardiac, cerebral, lung and renal ischaemia–reperfusion (I/R) injuries. However, the effect of ALDH2 in intestinal I/R is unknown. The present study was set up to determine whether an ALDH2 agonist, Alda-1, could alleviate intestinal injury after gut I/R. In a mouse model of intestinal I/R injury, histological grading, proinflammatory cytokines, oxidative stress, cellular apoptosis, chemokine contents, ALDH2 activity, 4-hydroxy-trans-2-nonenal (4-HNE) and malondialdehyde (MDA) were evaluated. The results indicated that I/R treatment conferred elevation in pathological scores, proinflammatory cytokines, oxidative stress, cellular apoptosis and chemokine levels, accompanied by accumulated 4-HNE and MDA. No significant changes in ALDH2 activity were observed after I/R. However, Alda-1 pretreatment significantly decreased these injurious indicators, concomitant with up-regulated ALDH2 activity, and lessened 4-HNE and MDA accumulation. Taken together, our results implicate activation of ALDH2 by Alda-1 in the significant abatement intestinal I/R injury.